2009
DOI: 10.1142/s0218127409024761
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Dynamics for Maps in One and Two Dimensions: A Geometrical Method and Applications to Economics

Abstract: This article describes a method — called here "the method of Stretching Along the Paths" (SAP) — to prove the existence of chaotic sets in discrete-time dynamical systems. The method of SAP, although mathematically rigorous, is based on some elementary geometrical considerations and is relatively easy to apply to models arising in applications. The paper provides a description of the basic mathematical ideas behind the method, as well as three applications to economic models. Incidentally, the paper also discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 37 publications
2
76
0
Order By: Relevance
“…Medio et al 2009) Consider (J , d) a metric space and D an open set. We say that a continuous map ψ : D −→ J induces chaotic dynamics on two symbols if there exist two disjoint compact sets K 0 , K 1 ⊂ D such that, for each two-sided sequence (s i ) i∈Z ∈ {0, 1} Z , there exists a corresponding sequence (ω i ) i∈Z ∈ (K 0 ∪ K 1 ) Z such that…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Medio et al 2009) Consider (J , d) a metric space and D an open set. We say that a continuous map ψ : D −→ J induces chaotic dynamics on two symbols if there exist two disjoint compact sets K 0 , K 1 ⊂ D such that, for each two-sided sequence (s i ) i∈Z ∈ {0, 1} Z , there exists a corresponding sequence (ω i ) i∈Z ∈ (K 0 ∪ K 1 ) Z such that…”
Section: Appendixmentioning
confidence: 99%
“…Although numerical results have already suggested that the seasonal forced SIR model can exhibit chaotic dynamics, a rigorous proof was not given before. There are two main ingredients in our arguments: some subtle singular rescalings inspired by Smith (1983) and the method of stretching along the paths developed by Zanolin and his co-workers (Medio et al 2009;Margheri et al 2010Margheri et al , 2013Ruiz-Herrera and Zanolin 2014).…”
Section: Introductionmentioning
confidence: 99%
“…one of the trademarks of chaos. Another attempt would consist in using the 'stretching along the paths' (from now on, SAP) method, already employed, for instance, in [12,17] to prove the existence of chaotic dynamics for both discrete and continuous-time dynamical systems. A third approach would consist in working with the first three iterates of map f in (2.7), in order to find suitable intervals where to apply Theorem 1 in [10] to prove the existence of chaos in the sense of Li -Yorke, as described in conditions (T1) and (T2) in that result.…”
Section: Chaotic Dynamicsmentioning
confidence: 99%
“…Nonetheless, as seen in Proposition 4.1, the method in [7] still allows to draw some interesting conclusions from a dynamical viewpoint. For a more detailed comparison between the covering relations in [7,12], we refer the interested reader to [16].…”
Section: Chaotic Dynamicsmentioning
confidence: 99%
“…In Section 2 we recall the main topological tools which are used in the proof of our theorems. Namely, we give a brief survey of the so-called stretching along the paths (SAP) method introduced in [13] and further developed in a series of articles [12], [14], [15], [16]. Section 3 is devoted to the proof of Theorem 1 and to some of its immediate extensions.…”
Section: Introductionmentioning
confidence: 99%